Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1111/j.1365-313x.2010.04458.x
|View full text |Cite
|
Sign up to set email alerts
|

The plant ADH gene family

Abstract: SUMMARYThe structures, evolution and functions of alcohol dehydrogenase gene families and their products have been scrutinized for half a century. Our understanding of the enzyme structure and catalytic activity of plant alcohol dehydrogenase (ADH-P) is based on the vast amount of information available for its animal counterpart. The probable origins of the enzyme from a simple b-coil and eventual emergence from a glutathione-dependent formaldehyde dehydrogenase have been well described. There is compelling ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
125
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(132 citation statements)
references
References 134 publications
7
125
0
Order By: Relevance
“…Notung2.8 analysis using the ADH gene sequences suggested that the first ADH gene divergence event shown in Figure 3 by a circle separate monocot and dicots species from Papilionoideae species. The palms ADH proteins diverged within the monocots species (Figure 3) except WrADH and before the others monocots species (Figure 3) (Strommer, 2011). Our analysis revealed that in palms, the divergence of WrADH genes occurred after the others palms species diverged.…”
Section: Phylogenetic Analysesmentioning
confidence: 74%
See 1 more Smart Citation
“…Notung2.8 analysis using the ADH gene sequences suggested that the first ADH gene divergence event shown in Figure 3 by a circle separate monocot and dicots species from Papilionoideae species. The palms ADH proteins diverged within the monocots species (Figure 3) except WrADH and before the others monocots species (Figure 3) (Strommer, 2011). Our analysis revealed that in palms, the divergence of WrADH genes occurred after the others palms species diverged.…”
Section: Phylogenetic Analysesmentioning
confidence: 74%
“…The ADH genes in Arabidopsis thaliana (Innan et al, 1996), Arabidopsis gemmifera (Miyashita et al, 2013) and Leavenwortia in Brassicaceae, cottons (Small et al, 2000), and grasses Gaut et al, 1999) have been subjected to molecular evolutionary studies. However, the broader evolutionary histories of the ADH genes in the angiosperms remain unclear since few studies have investigated the evolution of the ADH genes in a wide range of angiosperms (Strommer, 2011).…”
Section: Author(s) Agree That This Article Remains Permanently Open Amentioning
confidence: 99%
“…Understanding the stress response mechanisms in plants therefore is a prerequisite for the development of new varieties of crops with durable levels of tolerance to these abiotic stresses. in both monocots and dicots including rice and Arabidopsis, the modes of expression of a large number of abiotic stress responsive genes, cDnAs and eSts (expressed sequence tags) have extensively been studied under various environmental conditions (3,9,13,14,19,20,24,25,28,31,35). Among them, DREB (dehydration responsive element binding) and CBF (c-repeat/DReB binding factor) genes, AOX (alternative oxidase) genes, genes involved in alcohol fermentation, dehydration and sugar metabolism are important players.…”
Section: Introductionmentioning
confidence: 99%
“…Genes involved in alcohol fermentation are known to respond to abiotic stresses. transcripts of ADH (alcohol dehydrogenase) and ALDH (aldehyde dehydrogenase) genes, which are involved in alcohol fermentation, are accumulated in response to abiotic stresses in rice and Arabidopsis thaliana (1,5,8,12,18,28). Abscisic acid (ABA) is a phytohormone regulating various abiotic stress responsive pathways (36).…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol dehydrogenases (ADH) is a group of Zn-binding enzymes which present in many organisms. The ADH family plays an important role in facilitating the interconversion between alcohols and *Address correspondence to this author at the State Key Laboratory of Resources and Environmental Information System, Institute of Geographical Sciences and Natural Resources Research, Chinese Academy of Sciences, China; Tel: 13911823799; E-mail: 596295719@qq.com aldehydes or ketones with nicotinamide adenine dinucleotide (NAD) as a coenzyme [5]. According to the previous reports, ADH family of plants has been observed to be involved in the biotic and abiotic stresses, such as disease resistance, drought tolerance, flooding resistance and so on [6].…”
Section: Introductionmentioning
confidence: 99%